2016
DOI: 10.1007/s11769-016-0804-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought on net primary productivity: Roles of temperature, drought intensity, and duration

Abstract: Northeast China has experienced frequent droughts over the past fifteen years. However, the effects of droughts on net primary productivity (NPP) in Northeast China remain unclear. In this paper, the droughts that occurred in Northeast China between 1999 and 2013 were identified using the Standardized Precipitation Evapotranspiration Index (SPEI). The NPP standardized anomaly index (NPP-SAI) was used to evaluate NPP anomalies. The years of 1999, 2000, 2001, and 2007 were further investigated in order to explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 43 publications
2
20
0
1
Order By: Relevance
“…And in recent 20 years, the risk of land surface drought increased (Burke & Brown, 2008). One aspect of precipitation changes, increased summer or growing season drought, which resulting from the global warming, probably leading the land surface more drying and will likely lower productivity in many areas (Dai, 2013;IPCC, 2013;Marvel et al, 2019), and these decreases will be caused by both the drought intensity and the duration (Ciais et al, 2005;Sun, Zhao, & Wang, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…And in recent 20 years, the risk of land surface drought increased (Burke & Brown, 2008). One aspect of precipitation changes, increased summer or growing season drought, which resulting from the global warming, probably leading the land surface more drying and will likely lower productivity in many areas (Dai, 2013;IPCC, 2013;Marvel et al, 2019), and these decreases will be caused by both the drought intensity and the duration (Ciais et al, 2005;Sun, Zhao, & Wang, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the magnitude of the response of vegetation to dry-wet conditions remains uncertain due to the complexity of the dry-wet transition and intrinsic drought sensitivity among vegetation types [21,43]. The intensity, duration, and timing of drought partly determine the effect of drought on vegetation productivity, where moderate drought with higher temperatures increases the net primary production (NPP), while severe drought causes a delayed response of NPP to precipitation [22,44]. As a satisfactory indicator of vegetation activities, the Normalized Difference Vegetation Index (NDVI), which was used in this study, has been widely and successfully used to detect the vegetation variations [36][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Extreme weather events (such as heavy rain or drought events) caused forest NPP to drop by more than 25% [16][17][18]. Sun et al concluded that drought events led to a decrease of 112.06 TgC in NPP in the northern part of China from 1999 to 2013 [19]. While extreme weather events (drought and heavy rain events) decreased NPP, levels recovered to their original values through self-growth in, showing that NPP has elasticity or resilience.…”
Section: Introductionmentioning
confidence: 99%